Efficacy and Safety of Ejiao (Asini Corii Colla) in Women With Blood Deficient Symptoms: A Randomized, Double-Blind, and Placebo-Controlled Clinical Trial - Zhang, Li; Xu, Zhongju; Jiang, Tao; Zhang, Jialu; Huang, Pinxian; Tan, Jiaqi; Chen, Gan; Yuan, Man; Li, Zhuo; Liu, Haibin; Gao, Dengfeng; Xiao, Lianbo; et al. (Frontiers in Pharmacology, 2021)
E-Jiao (Colla corii asini, donkey-hide gelatin) is a well-known traditional Chinese medicine, which has been widely used to nourish the blood, especially for women. The aim of this study was to assess the efficacy and safety of E-Jiao in blood-deficient patients. A total of 210 participants were recruited and randomly allocated into two groups, the placebo control group and E-Jiao treated group (6g/day). The primary outcomes on the efficacy of E-Jiao included TCM symptom scores, blood indicators and SF-36. The secondary outcomes were changes in fireness and safety evaluation. Results showed that after treatment with E-Jiao for 8 weeks, symptoms of dizziness significantly improved. Among the tested 24 blood biochemical parameters, the hematocrit and red blood cell number decreased in the placebo control group, but decreased significantly less in the E-Jiao treatment group. White blood cell and neutrophil counts increased in the E-Jiao group but within normal range. In addition, the quality of life was improved as the scores in SF-36 domains were significantly higher in the E-Jiao group. At the same time, there was no significant change in the Fire-heat Symptoms score or other safety parameters. Therefore, our study showed that E-Jiao has a promising effect in women suffering from blood deficiency without obvious adverse effects.